Formulasi Kebijakan Publik Tentang Penerapan Inovasi Daerah di Provinsi Sumatera Selatan - Nadelia Grasopa; Andries Lionardo; Raniasa Putra (Lembaga Teewan Journal Solutions, 2026)
This study aims to determine the formulation of public policy on regional innovation implementation in South Sumatra Province and to identify obstacles in formulating the policy. This descriptive qualitative research used primary and secondary data collected through literature and field studies. Data were collected from several government institutions and then analyzed using William Dunn's policy formulation stages: problem formulation, policy agenda, selection of alternative policies, and policy determination. The results indicate that the introduction and formulation of problems in regional innovation implementation have generally gone quite well, as shown by the identification of strategic issues and several studies compiled by Central and Regional Government institutions and BRIN. In its implementation, the South Sumatra Provincial Government has placed regional innovation as a priority agenda in the Regional Long-Term Development Plan, Regional Medium-Term Development Plan, and Annual Regional Government Work Plan. Subsequently, a grand design for regional innovation implementation has been produced as a derivative of these strategic plans.